Risk factors for mortality among Tanzanian infants and children - Rodrick R. Kisenge; Chris A. Rees; Jacqueline M. Lauer; Enju Liu; Wafaie W. Fawzi; Karim P. Manji; Christopher P. Duggan (Tropical Medicine and Health, 2020)
Abstract Background During the era of the Millennium Development Goals, under 5 mortality rates decreased significantly worldwide; however, reductions were not equally distributed. Children in sub-Saharan Africa still account for more than 50% of the world’s annual childhood deaths among children under 5 years of age. Understanding upstream risk factors for mortality among children may reduce the large burden of childhood mortality in sub-Saharan Africa. Our objective was to identify risk factors for mortality among infants and children in Tanzania. Methods We conducted a secondary analysis of data pooled from two randomized-controlled micronutrient supplementation trials. A total of 4787 infants were enrolled in the two trials (n = 2387 HIV-exposed and n = 2400 HIV-unexposed). Predictors of mortality were assessed using unadjusted and adjusted hazard ratios (aHRs). Results There were 307 total deaths, 262 (11%) among children who were HIV-exposed and 45 (2%) among children who were HIV-unexposed (P < 0.001). The most common cause of death was respiratory diseases (n = 109, 35.5%). Causes of death did not significantly differ between HIV-exposed and HIV-unexposed children. In adjusted regression analyses, children with birth weight <2500 g (aHR 1.75, 95% CI 1.21–2.54), Apgar score of ≤7 at 5 min (aHR 2.16, 95% CI 1.29–3.62), or who were HIV-exposed but not infected (aHR 3.35, 95% CI 2.12–5.28) or HIV-infected (aHR 27.56, 95% CI 17.43–43.58) had greater risk of mortality. Conclusions Infection with HIV, low birthweight, or low Apgar scores were associated with higher mortality risk. Early identification and modification of determinants of mortality among infants and children may be the first step to reducing such deaths.